New Acquisitions. (New York : Robert Elkon Gallery, 1969)
Arp ; Brauner ; Delvaux ; Dubuffet ; Giacometti ; Kupka ; Magritte ; Matisse ; Matta ; Miro ; Moholy-Nagy ; Mondrian ; Picabia ; Pollock ; Rodin ; Seligmann ; Tanguy
New Acquisitions, Robert Elkon Gallery, New York, September 27 - October 29, 1969
boek